Birds and bats contribute to natural regulation of the millet head miner in tree-crop agroforestry systems. (June 2020) - Sow, Ahmadou; Seye, Djiby; Faye, Emile; Benoit, Laure; Galan, Maxime; Haran, Julien; Brévault, Thierry
Abstract: A better understanding of environmental factors driving natural pest regulation is a major challenge for designing sustainable cropping systems. The objective of the present study was to assess the association between vegetation openness in traditional tree-crop agroforestry systems in Senegal, richness and abundance of vertebrates including insectivorous birds and bats, and their contribution to the natural regulation of crop pests. The millet head miner (MHM), Heliocheilus albipunctella (Lepidoptera, Noctuidae), a major constraint to increasing millet crop productivity in sub-Saharan Africa, was selected as a model system. Ten sites separated by at least one km from each other were selected in a 100 km 2 study area in the Peanut basin in Senegal. In each site, a pair of millet fields distant from at least 100 m each was selected according to a gradient of vegetation openness within a 100-m radius buffer with sampling plot (5 × 5 m) at the center. Nine insectivorous bird and bat species were recorded in millet fields over the 2017 cropping season and their predator status was confirmed by direct observation or DNA detection in fecal samples. Grain losses were reduced when panicles were accessible to birds and bats, confirming their net contribution to pest regulation. At a local scale, tree diversity and vegetation openness were important predictors of the abundance of insectivorous village weaver birds and grey-headed sparrows, respectively. Some tree species (soapberry trees and neems) indirectly contributed to natural regulation of the MHM likely by providing refuges to insectivorous vertebrates whereas other tree species (baobabs) provided disservices as possible refuges for the MHM moths. Further research is needed to better understand relationships between tree cover, food web interactions and natural pest suppression, so that specific conservation measures such as habitat management can be designed to improve pest control. Graphical abstract: Image 1 Highlights: Vertebrates, including birds and bats, are effective predators of the millet head miner. They contribute to natural pest control and reduction of millet grain loss. The abundance of insectivorous birds is enhanced by tree diversity at a local scale. The contribution of trees for natural pest control is species-dependent. Trees can serve as refuges for pest (eg. baobab/moths) and predators (eg. palm tree/bats or neem/village weavers).